Pengaruh Lingkungan Kerja dan Supervisi Akademik Kepala Sekolah terhadap Kinerja Guru - Sudarti, Yuli (Journal of Innovation in Teaching and Instructional Media, 2022)
One of the efforts that can be made by principals to improve teacher performance is to carry out academic supervision, namely guidance related to learning. This study aims to determine (1) the effect of academic supervision on teacher performance at SMPN 5 Prabumulih; (2) the influence of the work environment on the performance of teachers at SMPN 5 Prabumulih; (3) the influence of academic supervision and work environment on teacher performance at SMPN 5 Prabumulih. The results showed that academic supervision and work environment had an effect on teacher performance. Therefore, to improve teacher performance, it can be done by implementing academic supervision of the principal and paying attention to the work environment around the teacher.